1947
DOI: 10.1079/bjn19470030
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Balances during Recovery from Severe Undernutrition

Abstract: The results reported below were obtained on two groups of subjects, Group I in Western Holland in 1945 and Group I1 in the British Zone of Germany in 1946.Among the objects of the Dutch investigation was the determination of the calorieand protein-intake levels which would secure optimum nitrogen retention and rapid increase in weight in severely undernourished patients. The later work in Germany had as one of its objects the determination of the calorie and protein-nitrogen intakes necessary to secure nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1950
1950
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Previous studies investigating whole-body protein turnover in the context of mixed macronutrient meal intake demonstrated that anabolic response is not limited by protein synthesis (82)(83)(84) . Deutz and Wolfe (85) advocated that there is no limit to in vivo whole-body protein anabolism when protein is consumed as a part of a mixed macronutrient meal (97,101) . More recently, Park et al (83) showed in healthy older adults (69•3 ± 1•8 years) that there is a higher MPS response following the consumption of a higher protein intake (70 g) compared with moderate (35 g) as part of a mixed macronutrient meal, and a greater whole-body net protein balance in the higher protein intake group due to the suppression of protein breakdown as well as increased protein synthesis (Fig.…”
Section: Protein Turnover Kinetic Measurementmentioning
confidence: 99%
“…Previous studies investigating whole-body protein turnover in the context of mixed macronutrient meal intake demonstrated that anabolic response is not limited by protein synthesis (82)(83)(84) . Deutz and Wolfe (85) advocated that there is no limit to in vivo whole-body protein anabolism when protein is consumed as a part of a mixed macronutrient meal (97,101) . More recently, Park et al (83) showed in healthy older adults (69•3 ± 1•8 years) that there is a higher MPS response following the consumption of a higher protein intake (70 g) compared with moderate (35 g) as part of a mixed macronutrient meal, and a greater whole-body net protein balance in the higher protein intake group due to the suppression of protein breakdown as well as increased protein synthesis (Fig.…”
Section: Protein Turnover Kinetic Measurementmentioning
confidence: 99%
“…In addition, as the protein intake was raised, the calorie intake was usually increased also; such caloric increments may also have tended to give falsely high values for nitrogen storage. The same criticisms may be directed at more recent studies (11)(12)(13)(16)(17)(18)(19)(20)(21) (12) have stated that the amount of nitrogen retention in malnourished men is related more specifically to calorie intake than nitrogen intake. The data used as the basis of the belief in the pre-eminent influence of calories on nitrogen metabolism are presented in Table 5 of Beattie, Herbert, and Bell's paper (12).…”
Section: Discussionmentioning
confidence: 93%
“…The same criticisms may be directed at more recent studies (11)(12)(13)(16)(17)(18)(19)(20)(21) (12) have stated that the amount of nitrogen retention in malnourished men is related more specifically to calorie intake than nitrogen intake. The data used as the basis of the belief in the pre-eminent influence of calories on nitrogen metabolism are presented in Table 5 of Beattie, Herbert, and Bell's paper (12). However, using these data, correlation of the per cent of absorbed nitrogen retained with the ratio of non-protein calories gives a correlation coefficient of -0.27 (p > 0.1).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations